Conformity to implicit social pressure: the role of political identity. (2nd July 2016) - Panagopoulos, Costas; van der Linden, Sander
Abstract: Although studies have shown that implicit social cues, such as images of watchful eyes, can elicit prosocial behavior, little research to date has examined individual differences in people's susceptibility to such subtle social cues. For example, individuals with a conservative ideology typically value social conformity, obedience, and adherence to social norms more than liberals. To examine partisan heterogeneity, we analyze data from two large randomized field experiments on voting behavior. Results suggest that the impact of eyespots on voter mobilization is indeed likely driven by political identity, with a significant effect for Republicans but not Independents or Democrats. These findings are consistent with an emerging line of research revealing individual differences in how susceptible humans are to implicit social cues.